WEBINAR EDUCATION TECHNOLOGY AND ITS CAPABILITIES (International journal of artificial intelligence, 2024)
this webinar provides a wide range of information about modern educational technologies and their capabilities in the educational process. New trends in educational technology, online educational platforms, digital resources and advantages and disadvantages of interactive teaching methods are discussed. The webinar also addresses the role of the webinar format in education, interactivity and opportunities for student engagement, as well as effective teaching strategies in a virtual educational environment.